Genomics-based assembly of a sorghum bicolor (L.) moench core collection in the Uganda national genebank as a genetic resource for sustainable sorghum breeding - Mufumbo, R.; Chakrabarty, S.; Nyine, M.; Windpassinger, S. M.; Mulumba, J. W.; Baguma, Y.; Odong, L. T.; Frisch, M.; Snowdon, R. J.; Justus Liebig University Giessen (My University, 2023)
The Uganda National GeneBank is a key reservoir of genetic diversity for sorghum (Sorghum bicolor (L.) Moench), with over 3333 accessions which are predominantly landraces (96.48%), but also includes the weedy accessions (0.63%), breeding lines (2.5%) and released varieties (0.39%). This genetic resource from the primary center of sorghum diversity and domestication is important for broadening the genetic diversity of elite cultivars through breeding. However, due to the large size of the collection, we aimed to select a core set that captures the maximum genetic and phenotypic diversity, in order to facilitate detailed genetic and phenotypic evaluation at a reduced cost. To achieve this, we genotyped the entire collection in 2020 using Diversity Array Technology sequencing (DArTseq). A total of 27,560 SNPs were used to select a core collection of 310 accessions using the GenoCore software. A comparison of core set and the whole collection based on the polymorphism information content, observed heterozygosity, expected heterozygosity and minor allele frequency showed no significant difference between the two sets, indicating that the core collection adequately captures the genetic diversity and allelic richness present in the whole collection. The core collection captures all the five major sorghum races and the 10 intermediate hybrids. The most strongly represented race is guinea (24.5%), while caudatum-bicolor is least frequent (0.69%). Landraces account for 92.2% of the core collection, whereas breeder’s lines, weedy accessions and released varieties contribute 2.2%, 3.5% and 1.9%, respectively.
Keywords: ddc:630